PENGGUNAAN MEDIA ALAT PERAGA SIKLUS AIR UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS V UPTD SD INPRES UMAPURA - Baharia Kasim; Nehemia Fanpada; Yessy Mata (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aimed to determine the effect of using a water cycle teaching aid on improving the learning interest of fifth-grade students at UPTD SD Inpres Umapura. The research employed a pre-experimental method using a one-group pretest-posttest design. The participants consisted of 16 fifth-grade students. Data were collected through observation and questionnaires. The data were analyzed using observation data analysis, learning interest questionnaire analysis, and the N-Gain test to determine the extent of the improvement in students' learning interest. The results showed an increase in students' learning interest after the implementation of the water cycle teaching aid, as indicated by the comparison of pretest and posttest questionnaire scores. The analysis revealed an average N-Gain score of 0.96, which falls into the high category, indicating a significant improvement in students' learning interest. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (H₀) was rejected. Based on these findings, it can be concluded that the water cycle teaching aid is effective and suitable for use in science learning to improve the learning interest of fifth-grade students at UPTD SD Inpres Umapura.